Telecommunications Network Design and Management - Anandalingam, G.; Raghavan, S. (Operations Research/Computer Science Interfaces Series, 2003)
Telecommunications Network Design And Management represents the state-of-the-art of applying operations research techniques and solutions across a broad spectrum of telecommunications problems and implementation issues. -The first three chapters of the book deal with the design of wireless networks, including UMTS and Ad-Hoc networks. -Chapters 4-6 deal with the optimal design of telecommunications networks. Techniques used for network design range from genetic algorithms to combinatorial optimization heuristics. -Chapters 7-10 analyze traffic flow in telecommunications networks, focusing on optimizing traffic load distribution and the scheduling of switches under multi-media streams and heavy traffic. -Chapters 11-14 deal with telecommunications network management, examining bandwidth provisioning, admission control, queue management, dynamic routing, and feedback regulation in order to ensure that the network performance is optimized. -Chapters 15-16 deal with the construction of topologies and allocation of bandwidth to ensure quality-of-service